1981
DOI: 10.1172/jci110072
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Vitamin D-binding Protein on the Serum Concentration of 1,25-Dihydroxyvitamin D3

Abstract: A B S T R A C T The influence of the serum binding protein (DBP) for vitamin D and its metabolites on the concentration of its main ligands, 25-hydroxyvitamin D3 (25-OHD3) and 1,25-dihydroxyvitamin D3 (1,25-[OHh2D3) was studied. The concentration of both 1,25-(OH)2D3 and DBP in normal female subjects (45±14 ng/liter and 333±58 mg/liter, mean+SD, respectively; n = 58) increased during the intake of estro-progestogens (69±27 ng/liter and 488±90 mg/liter, respectively; n = 29), whereas the 25-OHD3 concentration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
260
1
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(294 citation statements)
references
References 53 publications
29
260
1
3
Order By: Relevance
“…Consistent with this, a significant increase in the hourly fractional rate of radiocalcium absorption was found in 27 women with postmenopausal osteoporosis following 3 months of therapy with the anabolic steroid, nandrolone decanoate (92). However, since androgens may affect serum levels of vitamin D-binding protein, thus altering the levels of free 1,25-dihydroxyvitamin D 3 (93), it remains unclear whether androgens might exert their effects on intestinal calcium absorption directly or indirectly through effects on the vitamin D-endocrine system. Some studies also suggest that androgens may affect renal calcium transport.…”
Section: Extraskeletal Effects Of Androgens On Calcium Metabolismmentioning
confidence: 60%
“…Consistent with this, a significant increase in the hourly fractional rate of radiocalcium absorption was found in 27 women with postmenopausal osteoporosis following 3 months of therapy with the anabolic steroid, nandrolone decanoate (92). However, since androgens may affect serum levels of vitamin D-binding protein, thus altering the levels of free 1,25-dihydroxyvitamin D 3 (93), it remains unclear whether androgens might exert their effects on intestinal calcium absorption directly or indirectly through effects on the vitamin D-endocrine system. Some studies also suggest that androgens may affect renal calcium transport.…”
Section: Extraskeletal Effects Of Androgens On Calcium Metabolismmentioning
confidence: 60%
“…The majority of 25(OH)D circulates tightly bound to vitamin D-binding protein (VDBP) and more loosely bound to albumin; a much smaller percentage circulates free (31). Bioavailable 25(OH)D (the free plus albumin bound portions) has been proposed as a better indicator of vitamin D activity (32)(33)(34), possibly explaining discrepancies between findings of vitamin D effect on health outcomes in studies relying on total 25(OH)D. Several studies have identified a strong relationship between bioavailable vitamin D and indicators of vitamin D status such as bone mineral density and parathyroid hormone (32,33).…”
Section: Low Serum Concentrations Of Total 25-hydroxyvitamin D (25[oh]d)mentioning
confidence: 99%
“…Calcidiol (25- [17][18][19]. The free 1,25(OH) 2 D 3 index was calculated as the molar ratio of total 1,25(OH) 2 D 3 to DBP [20]. Serum intact parathyroid hormone (PTH (1-84)) was measured by a two-step immunochemical method, involving an aminoterminal capture and a midregional detecting antibody, as described previously [21].…”
Section: Biochemical Measuresmentioning
confidence: 99%